Microsoft's cunning plan. (Economist, 2001)
Facing its three chief challenges of the rise of the Internet, the slowing applications revenues, and the threat of a break-up, Microsoft, the world's biggest software firm, has a plan for dealing with these issues in the form of a new blueprint for the future of software. Revealed in summer 2000, the plan, called .NET, is nebulous in some parts and nonexistent in others, but it should come into focus over the next year. Furthermore, it may be able to solve all three of Microsoft's problems simultaneously. Microsoft's plan with .NET is to establish a new software platform. Rather than writing software for personal computers (PCs) that runs on Windows, the idea is that programmers will write Internet software that runs on .NET. As is the case with Windows, .NET will provide the basic blocks from which more complex software can be built. The major difference is that whereas PC software runs on a single machine, .NET software will involve interactions between numerous machines linked via the Internet and offering services to each other. The benefits for Microsoft of reorganizing itself around .NET are discussed.